A mutualistic interaction between Streptomyces bacteria, strawberry plants and pollinating bees - Da-Ran Kim (Nature Communications, 2019)
Microbes can establish mutualistic interactions with plants and insects. Here, Kim et al. show that Streptomyces bacteria can protect strawberry plants and honeybees from pathogens, can move into the plant vascular tissue from soil and from flowers, and are transferred among flowers by the pollinators.